Varieties of capital and gender party office in Italy. Issue 1 (February 2021) - Bordandini, Paola; Mulè, Rosa
Abstract : This article advances a new approach based on 'varieties of capital' to explain gendered upward mobility in political parties. Research on gender political advancement unduly neglects women delegates to national party congresses. Our work seeks to redress the imbalance by drawing on data gathered from 5, 122 questionnaires issued to national party delegates at 20 national conventions that took place between 2004 and 2013 in Italy. To analyse the data we develop a new framework based on 'varieties of capital'. Our approach builds on Bourdieu's three types of personal capital – economic, social and cultural – and interprets the findings borrowing analytical tools from recent feminist institutional theory, especially the concept of homosocial capital. Comparisons of male and female party delegates in terms of background and their political trajectories reveal the persistence of an uneven playing field, with gendered hierarchies in Italian political parties confirming an international pattern.